Study of reading habits 1984 - Stockholm - Weibull, Lennart (University of Gothenburg, 1993)
This survey forms part of the research program ´Dagspresskollegiet´. The target group of this survey was the inhabitants of Stockholm. Some of the questions are replications of questions asked in previous readership studies, i.e. questions concerning reading habits, subscriptions of papers, reading interests and background variables such as gender, age, education and party preference. There were also a number of questions not asked in previous surveys. The respondents were asked about the household´s media-equipment and use of video. There were also a battery of questions dealing with radio listening - amount, place, types of programs and broadcasting (national, provincial or local). Special attention was put on local radio and local-TV broadcasting and the respondents view on this new phenomena.

This survey forms part of the research program ´Dagspresskollegiet´. The target group of this survey was the inhabitants of Stockholm. Some of the questions are replications of questions asked in previous readership studies, i.e. questions concerning reading habits, subscriptions of papers, reading interests and background variables such as gender, age, education and party preference. There were also a number of questions not asked in previous surveys. The respondents were asked about the household´s media-equipment and use of video. There were also a battery of questions dealing with radio listening - amount, place, types of programs and broadcasting (national, provincial or local). Special attention was put on local radio and local-TV broadcasting and the respondents view on this new phenomena.
Läsvanestudien 1984 - Stockholm
Keywords: internal politics; inrikespolitik; Media; Media; Political behaviour and attitudes; Politiska beteenden och attityder; Leisure, tourism and sport; Fritid, turism och sport; Social Sciences; Samhällsvetenskap; Media and Communication Studies; Medie- och kommunikationsvetenskap